Penguatan Ekonomi Kreatif melalui Agrowisata Jagung dan Nilam di Iloheluma - Sunarty Suly Eraku; Mohamad Karmin Baruadi; Masruroh Masruroh (Universitas Negeri Gorontalo, 2026)
Iloheluma Village, Bone Bolango Regency, possesses considerable agricultural potential through corn and patchouli commodities; however, limited post-harvest processing, weak MSME management, and low product diversification have constrained local value creation. This community service program aimed to strengthen the village creative economy through the integration of corn and patchouli cultivation, product processing, business capacity building, and agrotourism-oriented promotion. The program was implemented over 45 days using a participatory approach involving lecturers, students, village government, farmer groups, and MSME actors through training, field demonstrations, mentoring, and evaluation activities. The results indicate improvements in community capacity regarding cultivation practices, product packaging and branding, digital promotion, and simple business bookkeeping. The program also encouraged the utilization of corn and patchouli as strategic resources for educational agrotourism and local economic development. Furthermore, the integration of agricultural production, product value addition, and community-based tourism strengthened collaboration among local stakeholders and provided an initial foundation for sustainable village economic development. The program demonstrates that an integrated agrotourism-based empowerment approach can support the development of rural creative economies through the optimization of local agricultural resources.